1990
DOI: 10.1111/j.1528-1167.1990.tb06306.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Clinicoelectrophysiologic Study of a Case of Lafora Disease Proven by Skin Biopsy

Abstract: A longitudinal clinicoelectrophysiologic study was undertaken of a 15-year 2-month-old girl with Lafora disease who was diagnosed by skin biopsy and an immunohistochemical method with antisera against Lafora bodies. From age 10 years 5 months, 4 months after onset, EEG disclosed progressive deterioration of background activity and incremental increase in epileptic discharges. Photosensitivity was unique: Occipital spikes and diffuse spike-wave discharges were provoked by low-frequency repetitive photic stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
2
18
0
8
Order By: Relevance
“…The LD is relatively frequent in southern Europe (Italy, France, and Spain), northern Africa, the Middle East, and south Asia (Serratosa et al 1995;Delgado-Escueta et al 2001). A few sporadic cases with typical LD phe-notype have also been reported from Japan and Korea (Kobayashi et al 1990;Kato et al 1999;Ganesh et al 2001;Ki et al 2003). A gene for LD was localized to a 3 cM region on 6q24 (Serratosa et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The LD is relatively frequent in southern Europe (Italy, France, and Spain), northern Africa, the Middle East, and south Asia (Serratosa et al 1995;Delgado-Escueta et al 2001). A few sporadic cases with typical LD phe-notype have also been reported from Japan and Korea (Kobayashi et al 1990;Kato et al 1999;Ganesh et al 2001;Ki et al 2003). A gene for LD was localized to a 3 cM region on 6q24 (Serratosa et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A anormalidade gênica subjacente foi mapeada para o cromossomo 6q24 9 . O aparecimento da doença (cerca de 85% dos casos) está fortemente relacionado a casamentos consanguíneos 2,5,10 . Vários estudos demonstraram a presença de deficiência da tirosina fosfatase, uma enzima relacionada ao metabolismo do glicogênio 9 .…”
Section: Discussionunclassified
“…No sistema nervoso central, os corpos de inclusão localizam-se, principalmente no núcleo denteado, núcleo rubro, substância negra e hipocampo 1 , embora também sejam encontrados na substância branca, nos nervos periféricos, miocárdio, musculatura esquelética, pele e fígado 5,8,11 . A biópsia profunda de pele parece ser o método mais indicado para o diagnóstico [10][11][12][13][14] . O EEG intercrítico mostra alentecimento da atividade de base, que apresenta-se nas frequências teta e delta.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In longitudinal studies of EEG, the pattern of spike and wave discharges at a frequency of 3 Hz, found in the early stages, increases to 6-12 Hz with disease progression [22].…”
Section: Clinical and Eletroencephalographic Aspectsmentioning
confidence: 99%